Effects of mid-respiratory chain inhibition on mitochondrial function in vitro and in vivo. Issue 1 (18th September 2015) - Broom, Ashley J.; Ambroso, Jeffrey; Brunori, Gino; Burns, Angie K.; Armitage, James R.; Francis, Ian; Gandhi, Mitul; Peterson, Richard A.; Gant, Timothy W.; Boobis, Alan R.; Lyon, Jonathan J.
Abstract : Schematic showing the toxicological and adaptive effects of drug-induced respiratory chain inhibition in vivo ; also highlighting unanticipated differences from observations made in vitro (in red). Abstract : Relating the in vitro mitochondrial effects of drug candidates to likely in vivo outcomes remains challenging. Better understanding of this relationship, alongside improved methods to assess mitochondrial dysfunction in vivo, would both guide safer drug candidate selection and better support discovery programmes targeting mitochondria for pharmacological intervention. The aim of this study was to profile the in vivo effects of a compound with suspected complex III electron transport chain (ETC) inhibitory activity (GSK932121A) at doses associated with clinical signs, and relate findings back to in vitro data with the same compound. Control liver mitochondria or HepG2 cells were treated in vitro with GSK932121A to assess mitochondrial effects on both calcium retention capacity (CRC) and oxygen consumption rate (OCR) respectively. The same assessments were then performed on liver mitochondria isolated from Crl:CD(SD) rats, 5 hours following intraperitoneal (IP) administration of GSK932121A. Lactate/pyruvate assessment, hepatic microscopy, blood gas analysis, glutathione profiling and transcriptomics were used to characterise the acute toxicity. In vivo, GSK932121A caused hypothermia, increased levels of hepatocellular oxidative stress and a metabolic shift in energy production, resulting in an increased lactate/pyruvate ratio, liver steatosis and glycogen depletion, together with gene expression changes indicative of a fasted state. As would be expected of an ETC inhibitor, GSK932121A reduced the CRC of liver mitochondria isolated from naive control animals and the OCR of HepG2 cells when treated directly in vitro. In contrast, mitochondria isolated from animals treated with GSK932121A in vivo unexpectedly showed an increase in CRC and basal OCR. Whilst seemingly contradictory, these differences likely reflect an adapted state in vivo resulting from the initial insult in combination with compensatory changes made by the tissue to maintain energy production. Only the initial, unconfounded, response is observable in vitro . These findings improve current understanding of the toxicological and molecular consequences of ETC inhibition. Furthermore, this work highlights key differences in the way that mitochondrial perturbation is manifest in vivo versus in vitro in terms of functional endpoints and helps guide endpoint selection for future studies with potential mitochondrial toxicants or drugs designed to modulate mitochondrial function for therapeutic benefit.